Analysis of exponential stability and L1-gain performance of positive switched impulsive systems with all unstable subsystems - Zhang, Xiukun; Sun, Yuangong; Zhu, Xingao (Nonlinear Analysis: Modelling and Control, 2025)
This article investigates the exponential stability and L1-gain performance of time-varying positive switched impulsive systems even when all modes are unstable. By employing the discretized switched copositive Lyapunov function approach and the analytical method developed for positive systems, we derive a sufficient condition to ensure the exponential stability for such systems. An algorithm for computing the stability region of admissible dwell time is also introduced. Furthermore, building on this stability result, the L1-gain performance of positive switched impulsive systems is further studied. Finally, numerical examples are presented to demonstrate the validity of our results.